RECQL5 at the Intersection of Replication and Transcription - Hamadeh, Zeid; Lansdorp, Peter (Frontiers in Cell and Developmental Biology, 2020)
Maintenance of genome stability is essential to prevent the accumulation of DNA mutations that can initiate oncogenesis and facilitate tumor progression. Studies of DNA repair genes have revealed a highly dynamic and redundant network of genes and proteins responsible for maintaining genome stability. Cancer cells are often deficient in DNA repair and the resulting genome instability decreases their fitness but also allows for more rapid evolution under selective pressure. Of particular interest for genome stability are the RecQ class of helicases. Five genes in this class, RECQL1, BLM, WRN, RECQL4 and RECQL5, are unique to mammals as simpler eukaryotes and bacteria appear to have only one homolog, RecQ. The precise role of each of the five mammalian RecQ helicases remains to be determined. Whereas loss of function mutations of BLM, WRN and RECQL4 in humans are associated with specific diseases, RECQL1 and RECQL5 have not yet been associated with specific disorders. Mice deficient in Recql5 are more likely to develop cancer and human cells deficient in RECQL5 display chromosomal instability and elevated sister chromatid exchange events similar to cells deficient in any of the other RecQ helicases. Recent studies support that RECQL5 can resolve intermediate DNA repair structures resulting from the collision of DNA transcription and replication machinery. In this review, we aim to summarize current knowledge regarding RECQL5 in the context of DNA repair, replication and transcription to help uncover the role of RECQL5 in maintenance of genome stability.